Anglicisms in French Vocabulary in the Early 21st Century - Lazarev, Artiom Valeryevitch (Journal of History Culture and Art Research, 2017)
The article examines the history and causes of the widespread use of Anglicisms in French. It also presents the views of French linguists concerning the mass penetration of English borrowings into the vocabulary of the French language. Examples are given of English borrowings from different parts of speech, of the ways of their penetration and the scope of functioning in modern French. The article also provides classification of Anglicisms, as well as some examples of their replacement by French words. Various forms of assimilation of Anglicisms in French, the phenomena of the parallel use of English borrowings and their French equivalents are considered. Examples are given of semantic, semantic-stylistic, and stylistic synonymy of French words and English borrowings. The author makes examples of regulatory documents aimed at slowing penetration of foreign vocabulary into French, of the facts of public response to the use of English borrowings in French. He concludes that the number of English borrowings will inevitably grow and that this vocabulary is necessary in modern French.